If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8a+3-5a-2a=0
We simplify the equation to the form, which is simple to understand
8a+3-5a-2a=0
We move all terms containing a to the left and all other terms to the right.
+8a-5a-2a=0-3
We simplify left and right side of the equation.
+1a=-3
We divide both sides of the equation by 1 to get a.
a=-3
| (X-1)+5+x=12 | | 2g+4=24 | | 5.7+6.6= | | (7x+15)=(10-9) | | 36x=8-14p | | 3=17-7n | | 14=4(7-8p)-6(4p-7) | | 250+14(h)=22(h) | | -y+3-3=-6 | | 5(2x-3)=7x+15 | | 11x-15=40 | | 3f-12=3(f+12) | | 5.25+15=46.50 | | 8x-3=3x-7 | | -4r+4r=8-4r+3r | | 130+40c=270 | | 4b-11=5 | | 15x-54=66 | | 3t^2-14t-22=0 | | (4x-1)(2x^2+3)= | | 64x^2-644x+1552=0 | | -6x+3=-39 | | .3x+5=6 | | k+9=6(k-1) | | 49=(-9y)-68 | | 130+40c=130 | | 3(4x^2-49)=27 | | 2-3x=x+y+2 | | 2+3ln(x+1)=4 | | -2v-4v=12 | | 12x+4[8-4(2x+4)]=4x-8 | | 8a-(-3-5a)= |